A handbook on multi-purpose cooperatives - Jadloc, Zosimo A. (1996)
This handbook is to guide individual leaders, different groups and communities in conceptualizing, understanding and operationalizing cooperative tested principles in their socio-economic projects.
Professorial Chair UPV Miag-ao, Iloilo
Keywords: Cooperative societies -- Cebu City; Cooperative societies -- Philippines